2020
DOI: 10.3390/ijms21103409
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Binding Proteins in Acute Leukemias

Abstract: Acute leukemias are genetic diseases caused by translocations or mutations, which dysregulate hematopoiesis towards malignant transformation. However, the molecular mode of action is highly versatile and ranges from direct transcriptional to post-transcriptional control, which includes RNA-binding proteins (RBPs) as crucial regulators of cell fate. RBPs coordinate RNA dynamics, including subcellular localization, translational efficiency and metabolism, by binding to their target messenger RNAs (mRNAs), thereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 252 publications
(312 reference statements)
0
37
0
Order By: Relevance
“…However, it mostly behaves as a tumor suppressor in acute leukemia [12]. RBPs constitute a key factor of the post-transcriptional process and play an important role in the regulation of RNA in gastrointestinal [13] and colorectal cancers [14].…”
mentioning
confidence: 99%
“…However, it mostly behaves as a tumor suppressor in acute leukemia [12]. RBPs constitute a key factor of the post-transcriptional process and play an important role in the regulation of RNA in gastrointestinal [13] and colorectal cancers [14].…”
mentioning
confidence: 99%
“…The fate of mature mRNA is affected by non-coding RNAs and RNA-binding proteins (RBPs). RBPs, such as transcription factor, is a crucial regulator for post-transcriptional regulation, and the regulation of the RBPs is highly dependent on the binding sequences [24]. Information on the studied SNPs assessed in Hap-loReg and Regulome DB datasets showed that rs4140535, rs1778258, rs17273700, rs1228814, rs11568817, and rs130058 were all overlap in regions with promoter or enhancer function in tissues such as the brain.…”
Section: Discussionmentioning
confidence: 99%
“…The fate of mature mRNA is affected by non-coding RNAs and RNA-binding proteins (RBPs). RBPs, such as transcription factor, is a crucial regulator for post-transcriptional regulation, and the regulation of the RBPs is highly dependent on the binding sequences [24]. Information on the studied SNPs assessed in HaploReg and Regulome DB datasets showed that rs4140535, rs1778258, rs17273700, rs1228814, rs11568817, and rs130058 were all overlap in regions with promoter or enhancer function in tissues such as the brain.…”
Section: Discussionmentioning
confidence: 99%